2011
DOI: 10.1002/ajh.22050
|View full text |Cite
|
Sign up to set email alerts
|

POEMS syndrome: 2011 update on diagnosis, risk‐stratification, and management

Abstract: Disease overviewPOEMS syndrome is a paraneoplastic syndrome due to an underlying plasma cell neoplasm. The major criteria for the syndrome are polyradiculoneuropathy, clonal plasma cell disorder (PCD), sclerotic bone lesions, elevated vascular endothelial growth factor, and the presence of Castleman disease. Minor features include organomegaly, endocrinopathy, characteristic skin changes, papilledema, extravascular volume overload, and thrombocytosis. Diagnoses are often delayed because the syndrome is rare an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 138 publications
2
87
0
8
Order By: Relevance
“…It is reported that combination of CY and prednisone is an effective treatment regimen for patients with POEMS syndrome. 1 In addition, Jimenez-Zepeda et al 18 reported that short-term induction therapy of CY and prednisone before transplantation could significantly decrease the incidence of engraftment syndrome and reduce transplant-related mortality. Therefore, pretreatment with high dose of CY might decrease the level of pro-inflammatory cytokines, relieve disease activity and reduce G-CSF-related adverse effects, which might improve the efficacy and safety of mobilization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is reported that combination of CY and prednisone is an effective treatment regimen for patients with POEMS syndrome. 1 In addition, Jimenez-Zepeda et al 18 reported that short-term induction therapy of CY and prednisone before transplantation could significantly decrease the incidence of engraftment syndrome and reduce transplant-related mortality. Therefore, pretreatment with high dose of CY might decrease the level of pro-inflammatory cytokines, relieve disease activity and reduce G-CSF-related adverse effects, which might improve the efficacy and safety of mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Additional features include papilledema, extra-vascular volume overload, sclerotic bone lesions and Castleman's disease. 1,2 The pathogenesis of POEMS syndrome is not fully understood, but there is increasing evidence suggesting that high levels of serum vascular endothelial growth factor (VEGF) may contribute to certain features of POEMS syndrome such as extra-vascular volume overload, organomegaly and hemangioma. The course of POEMS syndrome is chronic and the median survival is usually 45 years.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two other patients using it as "salvage" improved, but relapsed and died despite continued therapy, normal VEGF at 3.5 and 5.5 years. Six other cases of use with or after other alkylator based therapy yielded one death and 4 patients with improvement [22][23][24][25][26][27]176] High-dose chemotherapy with peripheral blood stem cell transplant can also be quite effective, but selection basis may confound these reports. Case series suggest 100% of patients achieve at least some neurologic improvement [18,54,87,140,[149][150][151][152][153][154][155][156][181][182][183][184][185].…”
Section: Management Of Poems Syndrome With Disseminated Bone Marrow Imentioning
confidence: 99%